Incidence of injuries in professional snow sports: A systematic review and meta-analysis - Fu, X. L.; Du, L.; Song, Y. P.; Chen, H. L.; Shen, W. Q (Journal of Sport and Health Science, 2022)
Purpose The study aimed to conduct a comprehensive systematic review and meta-analysis of injury incidence in professional skiers and snowboarders.